EVALUATING THE READINESS FOR ISO 9001:2015 CERTIFICATION: A CASE STUDY - Omallao, Oriel; Gano-an, Jonathan (Universitas Pelita Harapan, 2024)
This quantitative exploratory paper evaluates the degree of adoption of a cooperative to Total Quality Management (TQM) practices as a precursor study for its readiness for ISO 9001:2015 Quality Management System certification. Questionnaires were developed to explore practices already implemented within the ambit of TQM. Selected participants were grouped into two: (1) Management which is the middle-level management up to the CEO and (2) Governance composed of the Board of Directors, elected and appointed officers. A total number of 37 respondents were surveyed simultaneously. Primary data gathered from survey questionnaire were tested statistically for non-parametric datasets using SPSS16 for descriptive statistics and test of normality. Test statistics using Mann-Whitney U Test examines if the adoption of Quality Management Principles (QMPs) of ISO 9001-2015 is equally perceived by the two variable groupings. The study concluded that the seven QMPs are somewhat adopted based on the result of the overall mean score. Results of descriptive statistics for each of the QMP revealed that Leadership has the highest mean. Whereas other QMPs such Customer Focus, Improvement, Process Approach, Evidence-Based Decision Making, Engagement of People, and Relationship Management are somewhat adopted. Results of Mann-Whitney U Test revealed that TQM adoption is perceived more by the Governance group than by the Management group and the two variable groupings have differing perceptions on the adoption of TQM, thus rejecting the null hypothesis of similarity among the two groups. Abstrak dalam Bahasa Indonesia. Makalah eksploratif kuantitatif ini mengevaluasi tingkat adopsi suatu koperasi terhadap praktik Total Quality Management (TQM) sebagai studi pendahuluan untuk kesiapan sertifikasi Sistem Manajemen Mutu ISO 9001:2015. Kuesioner dikembangkan untuk mengeksplorasi praktik yang telah diimplementasikan dalam lingkup TQM. Peserta yang dipilih dibagi menjadi dua kelompok: (1) Manajemen yang terdiri dari manajemen tingkat menengah hingga CEO dan (2) Tata Kelola yang terdiri dari Dewan Direksi, pejabat terpilih, dan diangkat. Sebanyak 37 responden disurvei secara bersamaan. Data primer yang dikumpulkan dari kuesioner survei diuji secara statistik untuk dataset non-parametrik menggunakan SPSS16 untuk statistik deskriptif dan uji normalitas. Uji statistik menggunakan Uji Mann-Whitney untuk memeriksa apakah adopsi Prinsip Manajemen Mutu (QMP) ISO 9001-2015 sama-sama dirasakan oleh dua kelompok variabel. Studi ini menyimpulkan bahwa ketujuh QMP sedikit diadopsi berdasarkan hasil skor rata-rata keseluruhan. Hasil statistik deskriptif untuk masing-masing QMP mengungkapkan bahwa Kepemimpinan memiliki rata-rata tertinggi. Sedangkan QMP lainnya seperti Fokus pada Pelanggan, Peningkatan, Pendekatan Proses, Pengambilan Keputusan Berbasis Bukti, Keterlibatan Masyarakat, dan Manajemen Hubungan sedikit diadopsi. Hasil Uji Mann-Whitney menunjukkan bahwa adopsi TQM lebih dirasakan oleh kelompok Tata Kelola daripada kelompok Manajemen, dan kedua kelompok variabel memiliki persepsi yang berbeda tentang adopsi TQM, sehingga menolak hipotesis nol tentang kesamaan di antara kedua kelompok.